An Efficient Solvent-Free Microwave-Assisted Synthesis of Cinnamamides by Amidation Reaction Using Phenylboronic Acid/Lewis Base Co-catalytic System - Khaldoun, Khadidja; Safer, Abdelmounaim; Saidi-Besbes, Salima; Carboni, Bertrand; Le Guével, Rémy; Carreaux, François (Synthesis, 2019)
A microwave-assisted dehydrative amide condensation reaction is reported as an efficient access to cinnamamide derivatives under solvent-free conditions. This protocol between conjugated carboxylic acids and amines is based on the use of a co-catalytic system, including the presence of the commercially available phenylboronic acid and 4-(N,N-dimethylamino)pyridine N-oxide (DMAPO), with a complete chemoselectivity in favor of the corresponding α,β-unsaturated amides. The implementation of the reaction needs no special precaution, and less reactive amines, such as substituted anilines, are also efficient under these conditions. A series of novel conjugated amides have been evaluated for their cytotoxic activities against several human cancer cell lines.
Keywords: cinnamamide derivatives; direct amide formation; boronic acid; microwave heating; catalytic system